JADIDIST MOVEMENT IN TURKESTAN AND ITS HISTORY (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the historical importance of the Jadidism movement, its scientific and educational heritage, and the issues of revival of this heritage after Uzbekistan gained independence. Also, the role of the Jadids in the national revival, reform of the education system and the development of the society will be highlighted.
Keywords: Uzbekistan, Turkestan, modernism, enlightenment, independence, national revival, scientific heritage, educational reform, newspaper, magazine, representatives of modernism.